Kelemahan Metode Enkripsi Message Digest 5 Terhadap Kriptanalisis Modern - Asep Muhidin (Teknik Informatika, Universitas Pelita Bangsa, 2020)
This study examines encryption techniques using the MD5 method. So popular is this method that after several decades of its release this method is still often used, even though a year since its release was announced about the potential weaknesses of this method. The discussion of weaknesses in the MD5 method in this study is referring to research conducted by Dobertin H. About the potential errors in this method. This study examines the weakness of encryption techniques using the MD5 method that has been published by other studies before. The results and conclusions in this study can be used as a reference for information system makers to pay attention to the aspect of data security and make modifications in such a way as to prevent the potential weaknesses discussed in this study. Keywords: Cryptography, Data security, MD5, MD5 potential weaknesses